Marketing Public Relations Sang Pisang Dalam Menambah Brand Awareness - Rany Syaamila; Syifa Astasia Utari (Institut Teknologi dan Bisnis Semarang, 2024)
Sang Pisang is a food and beverage business owned by President Jokowi's son, Kaesang Pangarep, together with a businessman from Makassar, Ansari Kadir. Sang Pisang was born in 2017 by serving products made from bananas. Sang Pisang just rebranded in November 2022 by presenting the latest concept, namely changing the outlet, logo, visuals, packaging design, and presenting several new menu variations, so there is a need for activities that can increase brand awareness. Sang Pisang carries out marketing implementation using marketing public relations to provide communication to its consumers that is educational and informative using social media and several offline activities. The purpose of this research is to find out how Sang Pisang implements marketing public relations in increasing brand awareness. The theory used in this research is Marketing Public Relations (Kotler and Keller, 2012). The approach used in conducting this research is a qualitative approach with descriptive methods, and data collection techniques through observation, interviews and documentation. The results of this research show that Sang Pisang's Marketing Public Relations is carried out with various strategies such as Publication using social media, events, press conferences and podcasts, Media Identity by making changes to the logo, visuals and outlets. , Marketing Public Relations Activity (Marketing Public Relations Activities) for online using social media such as Twitter, Tiktok, and Instagram while offline, namely by holding press conferences, events, Corporate Social Responsibility (CSR), and podcasts, Public-Services Activity ( Public Activity Services) by carrying out CSR such as Samtama activities, donations, and several other humanitarian assistance have succeeded in increasing Brand Awareness